The Analysis of Palm Oil Commodities and Impact on the Sustainability of Community Welfare - Zulkarnain Nasution; Meisa Fitri Nasution (Universitas Gorontalo, 2020)
The research was conducted to discover the impact of the existence of palm oil plantations on the economy and welfare of the community at Labuhanbatu. The type of data used in this research was the secondary data obtained from BPS, the research method used in this research was descriptive method, which described the problems in the field and then analyzed according to the facts. While the analytical tool to determine the impact of the economy on welfare was used SPSS version 22 to answer the hypothesis of palm oil plantations. The results showed that the variables of poverty, underprivileged families, plantation GRDP, processing industry GRDP, protected forests, community forests, and determinants of rice fields have an economic and welfare impact of 0.949. of palm oil plantations affected the increasing of socio-economic conditions of the community. So that the level of welfare of the community may increase. Cointegration test results showed that there was an economic impact of the increasing palm oil plantations on the level of community welfare by looking at the HDI data of Labuhanbatu through economic growth